The effect of dental bleaching on pulpal tissue response in a diabetic animal model: a study of immunoregulatory cytokines - Ferreira, L. L. [UNESP]; Gomes-Filho, J. E. [UNESP]; Benetti, F. [UNESP]; Carminatti, M. [UNESP]; Ervolino, E. [UNESP]; Briso, A. L.F. [UNESP]; Cintra, L. T.A. [UNESP] (Wiley, 2018)
Aim: To evaluate the influence of tooth bleaching on immunoregulatory cytokines production (IL-6, Tumour necrosis factor (TNF)-α and IL-17) in the pulp tissue of normoglycaemic and diabetic rats. Methodology: Twenty-eight rats were divided into normoglycaemic and diabetic rats (n = 14). Diabetes mellitus (DM) was induced with a single dose of alloxan diluted in citrate buffer via intramuscular injection. After DM confirmation, all rats were sedated and tooth bleaching was performed using 35% hydrogen peroxide on the right maxillary molars for 30 min. Left molars were used as controls. Bleaching resulted in four hemimaxillae groups: normoglycaemic (N), N-bleached (NBle), diabetic (D) and D-bleached (DBle). After 2 and 30 days, rats were euthanized and hemimaxillae processed for analysis by haematoxylin and eosin and immunohistochemistry. Results within and between animals were submitted to Wilcoxon signed-rank and Mann–Whitney tests (P < 0.05). Results: At 2 days, the NBle group had mild, and the DBle had severe inflammatory infiltration in the pulpal tissue (P < 0.05). TNF-α and IL-6 cytokines were associated with increased immunolabelling in the bleached groups compared to nonbleached (P < 0.05). However, IL-17 had increased immunolabelling in the NBle compared to the N and DBle group (P < 0.05). At 30 days, reactionary dentine was observed in the coronal pulp of all bleached teeth and no inflammation was present (P > 0.05). TNF-α cytokines had increased immunolabelling in the DBle group compared to the D group (P < 0.05). However, for IL-6 and IL-17, no difference was observed in this period (P > 0.05). Conclusions: Tooth bleaching increased IL-6 and TNF-α in the pulp tissue regardless of diabetes mellitus; however, diabetic rats had higher TNF-α levels for longer periods. Tooth bleaching influenced the increase in IL-17 in the early periods in normoglycaemic rats.
Keywords: dental bleaching; diabetes mellitus; inflammatory response; proinflammatory cytokines